Confirming pericardial access by using impedance measurements from a micropuncture needle. Issue 6 (7th May 2020) - John, Mathews; Post, Allison; Burkland, David A.; Greet, Brian D.; Chaisson, Jordan; Heberton, George A.; Saeed, Mohammad; Rasekh, Abdi; Razavi, Mehdi
Abstract: Background: Pericardial access is complicated by two difficulties: confirming when the needle tip is in the pericardial space, and avoiding complications during access, such as inadvertently puncturing other organs. Conventional imaging tools are inadequate for addressing these difficulties, as they lack soft‐tissue markers that could be used as guidance during access. A system that can both confirm access and avoid inadvertent organ injury is needed. Methods: A 21G micropuncture needle was modified to include two small electrodes at the needle tip. With continuous bioimpedance monitoring from the electrodes, the needle was used to access the pericardium in porcine models (n = 4). The needle was also visualized in vivo by using an electroanatomical map (n = 2). Bioimpedance data from different tissues were analyzed retrospectively. Results: Bioimpedance data collected from the subcutaneous space (992.8 ± 13.1 Ω), anterior mediastinum (972.2 ± 14.2 Ω), pericardial space (323.2 ± 17.1 Ω), mid‐myocardium (349.7 ± 87.6 Ω), right ventricular cavity (235.0 ± 9.7 Ω), lung (1142.0 ± 172.0 Ω), liver (575.0 ± 52.6 Ω), and blood (177.5 ± 1.9 Ω) differed significantly by tissue type ( P < .01). Phase data in the frequency domain correlated well with the needle being in the pericardial space. A simple threshold analysis effectively separated lung (threshold = 1120.0 Ω) and blood (threshold = 305.9 Ω) tissues from the other tissue types. Conclusions: Continuous bioimpedance monitoring from a modified micropuncture needle during pericardial access can be used to clearly differentiate tissues. Combined with traditional imaging modalities, this system allows for confirming access to the pericardial space while avoiding inadvertent puncture of other organs, creating a safer and more efficient needle‐access procedure.